Weakly-crystallized biphase calcium phosphate artificial bone with high osteogenic activity as well as preparation method and application thereof

Through high-temperature sintering and cold isostatic molding, high-corrosion activity weak crystallized biphasic calcium phosphate artificial bone was prepared, solving the problem of balance between the osteogenesis speed and the osteotomy resorption speed in bone defect repair, and achieving excellent degradation and osteogenesis performance of the material.

CN119591397APending Publication Date: 2025-03-11THE THIRD AFFILIATED HOSPITAL OF SOUTHERN MEDICAL UNIV (ACAD OF ORTHOPEDICS GUANGDONG PROVINCE)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411552658.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a perfect balance between the osteogenesis speed and the osteoclastic resorption speed of calcium phosphate materials in bone defect repair, and it is difficult to degrade high-crystalline calcium phosphate materials and have poor biological activity.

Method used

High-temperature sintering is used to treat weak crystallized biphasic calcium phosphate powder, increase density through cold isostatic molding, and control the low-temperature sintering temperature to regulate the crystallinity, and prepare high-oscopic activity weak crystallized biphasic calcium phosphate artificial bone.

Benefits of technology

It is significantly better than the degradation and osteogenic properties of traditional high-crystalline biphasic calcium phosphate, has better biocompatibility and bone repair effect, and avoids the problem of increased crystallinity caused by high-temperature sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591397A_ABST
    Figure CN119591397A_ABST
Patent Text Reader

Abstract

The invention discloses high-osteogenic-activity weak-crystallization biphase calcium phosphate artificial bone meal as well as a preparation method and application thereof. The invention relates to a preparation method of a weakly-crystallized biphase calcium phosphate artificial bone, which comprises the following steps: carrying out compression molding on weakly-crystallized biphase calcium phosphate powder to obtain a blocky blank, crushing and sieving the blocky blank to obtain sieved particles, heating, and sintering at 700-900 DEG C to obtain the weakly-crystallized biphase calcium phosphate artificial bone. According to the invention, weakly-crystallized biphase calcium phosphate powder is subjected to pre-pressing molding and cold isostatic pressing secondary molding to obtain a block-shaped green body, and the block-shaped green body is crushed, screened and sintered to obtain the weakly-crystallized biphase calcium phosphate ceramic particle artificial bone. According to the artificial bone, the degradation performance of the biphase calcium phosphate is remarkably improved, and the osteogenic activity of the material is improved, so that the artificial bone has application potential in the aspect of bone defect filling and repairing biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials for repairing bone defects, and in particular relates to highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone powder, and a preparation method and application thereof. Background Art

[0002] Calcium phosphate materials are currently the most ideal bone repair materials because of their composition and structure that are close to natural bones, and have been widely used in this field. Common β-tricalcium phosphate (β-TCP), hydroxyapatite (HA) of different crystallinity, and biphasic calcium phosphate composed of the two all have certain bone repair capabilities, but it is difficult to achieve a perfect balance between the rate of osteogenesis and the rate of osteoclast absorption. HA has good mechanical properties, stability, and osteoconductivity, while β-TCP is more soluble and has osteoinductive ability. A suitable balance point can be found to adjust the mechanical properties, osteogenic activity, and absorbability of calcium phosphate.

[0003] In addition, the crystallinity of calcium phosphate represents the orderliness of its atomic arrangement, and the degree of crystallinity also affects the surface properties, degradation properties and biological properties of calcium phosphate. Low-crystallinity HA has better protein adsorption and sustained-release properties, but its excessive solubility may also inhibit the proliferation activity of cells. High crystallinity will make calcium phosphate difficult to degrade and have poor biological activity. Therefore, a lot of research is still needed on the effect of crystallinity on the biological properties of calcium phosphate materials and the optimization of the optimal crystallinity. After optimizing the physical ratio of calcium phosphate, further regulating its crystallinity may make its various properties more adaptable.

[0004] When biphasic calcium phosphate is used as a bone defect repair or replacement material in clinical practice, it needs to be implanted in the body in the form of stone, microspheres or granular artificial bone, otherwise it is easy to cause inflammatory reaction (Groot K D. Effect of Porosity and Physicochemical Properties on the Stability, Resorption, and Strength of Calcium Phosphate Ceramics [J]. Annals of the New York Academy of Sciences, 2010, 523 (Bioceramics: Material Characteristics Versus in Vivo Behavior): 227-233.). Biphasic calcium phosphate ceramic scaffolds are generally prepared by high-temperature sintering, however, this method is not suitable for the preparation of weakly crystalline biphasic calcium phosphate blocks, microspheres or granular artificial bones. Studies have shown that when the temperature of biphasic calcium phosphate reaches above 1000°C, the crystallinity will continue to increase and the grain size will increase, while the preparation of weakly crystalline biphasic calcium phosphate blocks or granular bone repair materials has not been reported. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention aims to provide a weakly crystalline biphasic calcium phosphate artificial bone with high osteogenic activity and a preparation method and application thereof.

[0006] The purpose of the present invention is achieved by at least one of the following technical solutions:

[0007] The preparation method of weakly crystalline biphasic calcium phosphate artificial bone with high osteogenic activity comprises the following steps: taking weakly crystalline biphasic calcium phosphate powder and pressing and molding it to obtain a block blank; crushing the block blank; sieving the block blank to obtain sieved particles; heating the block blank; and sintering the particles at 700-900° C. to obtain the weakly crystalline biphasic calcium phosphate artificial bone.

[0008] In the present invention, the weakly crystalline biphasic calcium phosphate powder is pressed and molded, including pre-pressing and cold isostatic pressing secondary press molding, the pre-pressing pressure is 20-60MPa, and the holding time of the pre-pressing is 15-90s; the cold isostatic pressing secondary press molding pressure is 80-220MPa, and the holding time of the cold isostatic pressing secondary press molding is 2-10min.

[0009] Furthermore, the particle size of the particles after screening is 0.5-2.8 mm.

[0010] Furthermore, the sintering time is 1-3h.

[0011] Furthermore, the heating rate is 2-10°C / min.

[0012] In one embodiment, the weakly crystalline biphasic calcium phosphate powder is prepared by chemical precipitation followed by high temperature calcination. Specifically, a calcium source, a phosphorus source and water are uniformly mixed to obtain a reaction solution, the reaction solution is adjusted to alkalinity, stirred, aged, centrifuged to obtain a precipitate, washed, dried, and sintered to obtain the weakly crystalline biphasic calcium phosphate powder.

[0013] The molar ratio of the calcium source to the phosphorus source is 1.4-1.7: 1. The molar volume ratio of the calcium source to water is 0.05-0.25: 1 mol / L.

[0014] The calcium source is calcium nitrate; the phosphorus source is at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate; and the pH value of the reaction solution is 8-9.

[0015] In the present invention, ammonia water or sodium hydroxide aqueous solution can be used to adjust the pH value of the reaction solution to 8-9.

[0016] The stirring rate is 300-600r / min, and the stirring time is 15-45min.

[0017] The aging time is 24-72h.

[0018] The sintering temperature is 700-900°C.

[0019] Another object of the present invention is to provide a weakly crystalline biphasic calcium phosphate artificial bone prepared by the above preparation method.

[0020] Another object of the present invention is to provide the use of the above-mentioned weakly crystalline biphasic calcium phosphate artificial bone in the preparation of medical bone defect filling and repair materials.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0022] (1) The weakly crystalline biphasic calcium phosphate artificial bone prepared by the present invention has a composition of hydroxyapatite, which is closer to the inorganic components of natural human bones, and tricalcium phosphate, which is easier to degrade. At the same time, the lower crystallinity synergistically promotes the degradation of the material and the adhesion and osteogenic differentiation of bone marrow mesenchymal stem cells on the surface of the material, which is significantly better than the degradation performance and osteogenic performance of traditional high-crystalline biphasic calcium phosphate. Therefore, it has unique advantages and application potential as a bone defect repair material.

[0023] (2) The present invention does not need to undergo high-temperature sintering during the weakly crystalline biphasic calcium phosphate artificial bone process, which can avoid problems such as increased crystallinity during the high-temperature sintering process. In addition, the present invention can regulate the crystallinity of the final weakly crystalline biphasic calcium phosphate artificial bone by controlling the low-temperature sintering temperature.

[0024] (3) The present invention improves the density of the weakly crystalline two-phase calcium phosphate block body by cold isostatic pressing, thereby improving the strength of the weakly crystalline two-phase calcium phosphate after low-temperature sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the X-ray diffraction diagram of comparative example and embodiment 1 and embodiment 2.

[0026] Figure 2 The scanning electron microscope images are of the surfaces of the ceramic blocks of the comparative example and examples 1 and 2 before crushing.

[0027] Figure 3 This is a scanning electron microscope image of the weakly crystalline biphasic calcium phosphate powder of Example 1.

[0028] Figure 4 The graphs show the open porosity and volume density results of the high-crystallinity biphasic calcium phosphate granule artificial bone of the comparative example and the weakly crystalline biphasic calcium phosphate granule artificial bone of Examples 1 and 2.

[0029] Figure 5 The graph shows the cell proliferation results of mouse bone marrow mesenchymal stem cells after co-culture with the control example high crystallinity biphasic calcium phosphate granule artificial bone and Example 1 and Example 2 weak crystallinity biphasic calcium phosphate granule artificial bone for 1, 3, and 5 days.

[0030] Figure 6a , Figure 6b , Figure 6c They are the result graphs showing the expression of genes related to osteogenic differentiation after co-culturing of mouse bone marrow mesenchymal stem cells with the control example high-crystalline biphasic calcium phosphate granule artificial bone, and the weakly crystalline biphasic calcium phosphate granule artificial bone of Example 1 and Example 2.

[0031] Figure 7 This is a morphology picture of the weakly crystalline biphasic calcium phosphate granular artificial bone prepared in Example 1.

[0032] Figure 8 The graphs show the results of new bone formation 4 and 8 weeks after the high-crystallinity biphasic calcium phosphate artificial bones of the comparative example and the weakly crystalline biphasic calcium phosphate artificial bones of Examples 1 and 2 were implanted into the femoral defects of rats. DETAILED DESCRIPTION

[0033] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.

[0034] Example 1

[0035] The weakly crystalline biphasic calcium phosphate powder was prepared by the following method: 14.66 g (0.111 mol) of diammonium hydrogen phosphate was weighed and added to 2000 mL of water to prepare a mixed aqueous solution A; 35.42 g (0.15 mol) of calcium nitrate was weighed and added to 2000 mL of water to prepare a mixed aqueous solution B; the mixed aqueous solution A was added dropwise to the mixed aqueous solution B, and stirring was continued at 400 r / min during the dropping process to obtain a reaction solution, and the pH value of the reaction solution was adjusted to 8 with ammonia water; after the dropping was completed, stirring was continued for 30 minutes at a stirring rate of 400 r / min to obtain a weakly crystalline biphasic calcium phosphate powder. Subsequently, the mixture was aged for 24 hours, the precipitate was centrifuged, washed and freeze-dried, and calcined at 700°C to obtain a weakly crystalline biphasic calcium phosphate powder.

[0036] The weakly crystalline biphasic calcium phosphate artificial bone is prepared as follows: weakly crystalline biphasic calcium phosphate powder is filled into a stainless steel mold, and pre-pressed by a press machine at a molding pressure of 30 MPa and a holding time of 60 seconds to obtain a pre-pressed green body; the pre-pressed green body is subjected to secondary cold isostatic pressing at a molding pressure of 220 MPa and a holding time of 2 minutes; the green body is then crushed and sieved with a standard sieve with a mesh size of 0.60 mm and 0.71 mm; finally, the sieved hydroxyapatite particles with a particle size of 0.60-0.71 mm are heated to 700°C at a heating rate of 5°C / min and calcined for 2 hours to obtain a weakly crystalline biphasic calcium phosphate artificial bone.

[0037] Example 2

[0038] The weakly crystalline biphasic calcium phosphate powder was prepared by the following method: 14.66 g (0.111 mol) of diammonium hydrogen phosphate was weighed and added to 2000 mL of water to prepare a mixed aqueous solution A; 35.42 g (0.15 mol) of calcium nitrate was weighed and added to 2000 mL of water to prepare a mixed aqueous solution B; the mixed aqueous solution A was added dropwise to the mixed aqueous solution B, and stirring was continued at 400 r / min during the dropping process to obtain a reaction solution, and the pH value of the reaction solution was adjusted to 8 with ammonia water; after the dropping was completed, stirring was continued for 30 minutes at a stirring rate of 400 r / min to obtain a weakly crystalline biphasic calcium phosphate powder. Subsequently, the mixture was aged for 24 hours, the precipitate was centrifuged, washed and freeze-dried, and calcined at 800°C to obtain a weakly crystalline biphasic calcium phosphate powder.

[0039] The weakly crystalline biphasic calcium phosphate artificial bone is prepared as follows: weakly crystalline biphasic calcium phosphate powder is filled into a stainless steel mold, and pre-pressed by a press machine at a molding pressure of 10 MPa and a holding time of 60 seconds to obtain a pre-pressed green body; the pre-pressed green body is subjected to secondary cold isostatic pressing at a molding pressure of 220 MPa and a holding time of 2 minutes; the green body is then crushed and sieved with a standard sieve with a mesh size of 0.60 mm and 0.71 mm; finally, the sieved hydroxyapatite particles with a particle size of 0.60-0.71 mm are heated to 700°C at a heating rate of 5°C / min and calcined for 2 hours to obtain a weakly crystalline biphasic calcium phosphate artificial bone.

[0040] Comparative Example

[0041] According to the calcium-phosphorus molar ratio of 1.55, 2000mL of diammonium hydrogen phosphate aqueous solution (0.075mol / L) was added dropwise to 2000mL of calcium nitrate aqueous solution (0.12mol / L). During the dropping process, stirring was continued at 400r / min for uniform stirring. At the same time, the pH value of the reaction solution was adjusted to 8.0 with ammonia water. After the addition was completed, stirring was continued for 120min for uniform stirring. Then, the solution was allowed to stand for 24h, and the precipitate was taken by centrifugation, washed and freeze-dried. Then, it was calcined at 1150°C with a heating rate of 5°C / min and a holding time of 2h. Finally, it was ground and sieved to obtain high-crystallinity biphasic calcium phosphate powder with a particle size of about 500nm.

[0042] The high-crystallinity biphasic calcium phosphate powder is filled into a stainless steel mold, and pre-pressed by a press machine at a molding pressure of 30 MPa and a holding time of 60 seconds to obtain a pre-pressed green body; the pre-pressed green body is subjected to secondary cold isostatic pressing at a molding pressure of 200 MPa and a holding time of 2 minutes; the green body is then crushed and sieved with standard sieves of 0.60 mm and 0.71 mm in size; finally, the sieved biphasic calcium phosphate particles with a particle size of 0.60-0.71 mm are heated to 1100°C at a heating rate of 5°C / min and calcined for 2 hours to obtain a high-crystallinity biphasic calcium phosphate artificial bone.

[0043] Experimental example:

[0044] 1. Crystallinity

[0045] X-ray diffractometer (XRD, D-5000 Bruker AXS) was used, with Cu-Kα emission source (wavelength ) Phase analysis was performed on Examples 1-2 and the comparative calcium phosphate ceramics. The scanning angle range was 10-70° (2θ).

[0046] The results show that the XRD diffraction patterns of Examples 1-2 and the comparative example were compared with the standard HA PDF card (JPCDS No.: 09-0432) and β-TCP PDF card (JPCDS No.: 09-0169), and it was found that the three groups of BCP ceramics were successfully prepared. More specifically, it can be clearly seen from the diffraction peak intensity of the XRD spectrum that there is a gradient change in the crystallinity of Example 1, Example 2 and the comparative example. Since CDHA (1.55Ca / P) with poor crystallinity is thermally decomposed at high temperature to obtain BCP, the Example 2 group still retains a certain amount of HA with poor crystallinity, and the half-maximum full width (FWHM) of its corresponding characteristic peak is large, indicating that its crystallinity is low. As the thermal decomposition temperature increases, the half-maximum full width (FWHM) of the corresponding characteristic peak of HA in the BCP ceramics of different cases also decreases accordingly, indicating that its crystallinity is gradually increasing. This further confirms that the present invention successfully prepared three groups of BCP ceramics with different crystallinity.

[0047] 2. Calcium phosphate ceramic grain morphology

[0048] 2.1 The ceramic sheets of Examples 1-2 and the comparative example were polished, thermally etched at 1000°C for 30 minutes, cooled, and then gold plated. The obtained morphologies were analyzed using a high-resolution field emission scanning electron microscope (FSEM; Merlin, Zeiss, Germany).

[0049] Figure 2 The results show that the BCP grains in each ceramic group are closely arranged together, and the grain size increases with the increase of crystallinity. It is worth noting that the grain size of the samples of Example 1 and Example 2 remains below 100 nanometers, so they are classified as nanoceramics. In addition, with the increase of crystallinity, the grain shape becomes more rounded. In addition, the grain size of the control group increases significantly, which may affect its physicochemical and biological properties.

[0050] 2.2 The BCP powders of Examples 1-2 and the comparative example were added to ethanol for ultrasonic dispersion and then dropped onto a copper sheet, followed by drying, gold spraying and analysis of the resulting morphology using a high-resolution field emission scanning electron microscope (FSEM; Merlin, Zeiss, Germany).

[0051] Figure 3 The results show that the general morphology and size of the BCP artificial bone powder in Example 1 can be seen. There are large round particles, which are presumed to be β-TCP, while the smaller grains may be undecomposed weakly crystalline HA.

[0052] 3. Porosity and volume density of calcium phosphate ceramics

[0053] The open porosity and bulk density of ceramics were determined using the Archimedean drainage method. The measurement process involves weighing the dry weight of the ceramic (m0) using an electronic balance, then immersing the ceramic in a beaker filled with anhydrous ethanol and maintaining it at a negative pressure of -100 kPa for 60 minutes to ensure that the ethanol completely penetrates into the pores of the ceramic. Subsequently, the floating weight of the ceramic in anhydrous ethanol is measured (m1). Finally, the excess liquid is removed from the ceramic support immersed in anhydrous ethanol, and its wet weight is measured in the air (m2). Using these data, we calculate the bulk density of the ceramic (ρ v ) and open porosity (P open ).

[0054]

[0055] P open =(m2-m1) / (m2-m0)×100%

[0056] The open porosity and relative volume density of BCP ceramics in different cases were determined by Archimedes drainage method. Figure 4 As shown. It can be seen that with the increase of BCP ceramic crystallinity, the porosity tends to decrease, while the bulk density shows the opposite trend. Obviously, the ceramic is sintered at high temperature, and the grains grow by melting and exclude pores. As the temperature increases, the grains are easier to sinter, so the porosity is lower.

[0057] 4. Cell Proliferation

[0058] The cytological properties of the material were evaluated using mouse bone marrow mesenchymal stem cells (mBMSCs, American Type Culture Collection, USA). The cells were cultured in high glucose medium (H-DMEM, Gibco, USA) containing 10 Vol% fetal bovine serum (FBS, Gibco, USA). Sterile ceramic sheets were placed in the culture dishes to ensure uniform distribution of cells. The cells were then cultured in a constant temperature incubator at 37°C and a carbon dioxide concentration of 5%. To maintain optimal conditions, the culture medium was changed every other day. The WST-8 experiment was performed using the CCK-8 kit (Dojindo Laboratory, Japan) to evaluate the proliferation of mBMSCs on the BCP ceramic surface in different cases. 2×10 4 The cells were seeded on the ceramic slides at a density of 10 cells / well, and the complete medium was removed after culturing for 1, 3, and 5 days. Finally, the absorbance of the supernatant was measured at a wavelength of 450 nm using a microplate reader.

[0059] Figure 5The results show the proliferation of mBMSCs on BCP ceramics in different cases after 1, 3, and 5 days of co-culture. On the first day of co-culture, there was no significant difference in the OD values ​​of all samples. However, on the third and fifth days of co-culture, the higher the crystallinity of the BCP ceramics, the higher the cell proliferation rate.

[0060] 5. Osteogenic Differentiation

[0061] The cell culture method still refers to the experimental method of experiment 4 above, except that the cells were cultured with osteogenic induction solution. After 7 days and 14 days of ceramic induction co-culture, the cells were gently rinsed three times with PBS and lysed. Subsequently, the mixture was purified using the HiPure Total RNA Micro Kit (magen, China). The obtained RNA was transcribed into cDNA using the iScript cDNA Synthesis Kit (Bio-Rad, USA) for PCR analysis. The expression levels of osteogenic genes (including ALP, type I collagen (Col-I) and osteocalcin (OCN)) were evaluated using Applied Biosystems QuantStudio 6Flex (ThermoFisher Scientific). The calculation formula for the relative content of the target gene is (ΔCt=Ct(target gene)-Ct(GAPDH), gene expression level=2 -ΔCt ).

[0062] The results showed that the expression of osteogenic-related genes in mBMSCs and BCP ceramic groups after 7 and 14 days of co-culture in different cases was similar. Figure 6a , Figure 6b , Figure 6c The results showed that when cultured for 7 days, ALP, Col-1 and OCN were significantly upregulated in Examples 1 and 2 compared with the control example, and the upregulation in Example 1 was the most obvious. When cultured for 14 days, the crystallinity dropped to the lowest point, that is, Example 1 showed a slight downregulation. By inducing osteogenic differentiation of mBMSCs in vitro, it was found that Examples 1 and 2 had a stronger ability to induce osteogenic differentiation, which was specifically reflected in Example 1.

[0063] 6. Biphasic calcium phosphate granules artificial bone morphology

[0064] The BCP ceramic blocks of Example 1-2 were crushed and sieved to obtain ceramic particles of relatively uniform size, and photographed with a high-power camera.

[0065] Figure 7 It can be seen that the prepared biphasic calcium phosphate particle artificial bone has a ceramic particle size range of 1.40mm-1.70mm.

[0066] 7. Bone repair effect

[0067] The bone repair model was performed using SD rats. The experimental subjects were adult female rats with a body weight of 250 ± 25 g and an age of 2 months. The implantation site was disinfected using 70% ethanol and 10% povidone-iodine (BetadineTM) solution. All animals underwent laparoscopic surgery under general anesthesia with 0.1 ml of sodium pentobarbital (Tokyo Chemical) per 100 g body weight. A circular defect (Φ3 mm × 3 mm) was created at the lateral hoof of the femur of the rats, and then the BCP ceramic samples of different cases were implanted, and the subcutaneous tissue and skin were sutured. To reduce the risk of infection, the rats were subcutaneously injected with penicillin antibiotics (Penicillin; Dayu Chemical Pharmaceutical) for three consecutive days after surgery at a dose of 40 mg / kg. The femurs of the implanted rats were harvested at the 4W and 8W culture period for further analysis, and 5 rats were sacrificed at each time point. After the rat femurs were removed, they were fixed in 10% formalin (BOSTER) at room temperature for 24 h. Then, micro-CT (SkyScan 1176, Bruker Micro-CT) was used to evaluate the osteogenesis around the ceramic implants. The images were reconstructed using the Feldkamp convolution back-projection algorithm, and the images were segmented into binary images using the adaptive local threshold method. The volume ratio of the new bone tissue around the ceramic (BV / TV) was calculated.

[0068] Bone regeneration in the femoral condylar defect was investigated by 3D computer modeling 4 and 8 weeks after implantation. At each time point after implantation, new bone formation was observed around the surface of the cylindrical specimen (green area). Figure 8 It shows that in the fourth week after implantation, both Example 1 and Example 2 had obvious new bone formation, but there was no significant difference between the two groups; however, the new bone in the example group was significantly more than that in the control group. In the eighth week after implantation, all experimental groups had more new bone formation. At the same time, it can still be seen that the degree of new bone formation in Example 1 and Example 2 was the highest, and it seems that between the two groups, the new bone in Example 1 group was slightly more than that in Example 2 group; but the amount of new bone in these two experimental groups far exceeded that in the control group, and the control group still had the least new bone.

Claims

1. A method for preparing a highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone, characterized in that: The weakly crystalline biphasic calcium phosphate powder is pressed and molded to obtain a block body, the block body is crushed and sieved to obtain sieved particles, and the temperature is increased and sintered at 700-900° C. to obtain the weakly crystalline biphasic calcium phosphate artificial bone.

2. The method for preparing the weakly crystalline biphasic calcium phosphate artificial bone with high osteogenic activity according to claim 1, characterized in that: The compression molding of the weakly crystalline biphasic calcium phosphate powder includes pre-compression molding and cold isostatic pressing secondary compression molding, the pre-compression molding pressure is 20-60MPa, and the pre-compression molding holding time is 15-90s; the cold isostatic pressing secondary compression molding pressure is 80-220MPa, and the cold isostatic pressing secondary compression molding holding time is 2-10min.

3. The method for preparing the highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone according to claim 1, characterized in that: The particle size of the sieved particles is 0.5-2.8 mm.

4. The method for preparing the highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone according to claim 1, characterized in that: The sintering time is 1-3h.

5. The method for preparing the highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone according to claim 1, characterized in that: The heating rate is 2-10°C / min.

6. The method for preparing the weakly crystalline biphasic calcium phosphate artificial bone with high osteogenic activity according to any one of claims 1 to 5, characterized in that: The weakly crystalline biphasic calcium phosphate powder is prepared by chemical precipitation followed by high temperature calcination.

7. The method for preparing the weakly crystalline biphasic calcium phosphate artificial bone according to claim 6, characterized in that: The calcium source, the phosphorus source and water are mixed uniformly to obtain a reaction solution, the reaction solution is adjusted to be alkaline, stirred, aged, centrifuged to obtain a precipitate, washed, dried, and sintered to obtain a weakly crystalline biphasic calcium phosphate powder.

8. The method for preparing the highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone according to claim 7, characterized in that: The molar ratio of the calcium source to the phosphorus source is 1.4-1.7:1; the molar volume ratio of the calcium source to water is 0.05-0.25:1 mol / L; The calcium source is calcium nitrate; the phosphorus source is at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate; the pH value of the reaction solution is 8-9; The stirring rate is 300-600r / min, the stirring time is 15-45min; the aging time is 24-72h; The sintering temperature is 700-900°C.

9. A weakly crystalline biphasic calcium phosphate artificial bone with high osteogenic activity obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The artificial bone is prepared by the preparation method of the weakly crystalline biphasic calcium phosphate artificial bone according to any one of claims 1 to 8.

10. Use of the highly osteogenic weakly crystalline biphasic calcium phosphate artificial bone according to claim 9 in the preparation of biomedical materials for filling and repairing bone defects.